Between arts-based methods and hermeneutics: Navigating the ethics of participation in research with vulnerable children - Catherine Huard; Prudence Caldairou-Bessette; Pierre Plante (Methods in Psychology)
Children are underrepresented in research, mainly because of the ethical issues that their participation raises. This is even more true when it comes to marginalized migrant children. For the sake of justice, researchers must think about methods for including children and their families and reflect on the ethics of knowledge building in these contexts. This article returns to the hermeneutics of Hans Georg Gadamer as an interpretation practice which values understanding rather than explanation. It also focuses on the concept of play which can be truth revealing and which is understood as the very being of artistic practices. This allows us to first emphasize the compatibility of hermeneutics and art-based approaches, and their ethical value when it comes to bringing clinical and research issues together. This article highlights that methods based on art and play itself are ethical in the way that they can both provide well-being and reveal a truth that is as useful to the participant as it is to the researcher. This article also addresses how the researcher, in the process of understanding, is “at play” in the research situation which places him in an active role. The play allows a participatory truth to emerge, a truth resulting from a dialogue. This leads us to recognize the ethical value of participation in research with children.